Sosialisasi Mitigasi Bencana Banjir Akibat Sampah pada Siswa Madrasah Jamiatul Islamiyah Kuripan - Iin Yulianti, M. A; Roky Zildan Finansyah; Yufita Dea Septiana; Yulfidha Diah Riama; Amir Mukhlisin; Fingkan Oktafiani; Nurul Pratiwi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
A lack of early environmental awareness is a primary contributing factor to flood disasters caused by waste accumulation in drainage systems. This community service project aimed to enhance flood disaster mitigation awareness and preparedness among 25–30 5th and 6th-grade students at MI Jamiatul Islamiyah. The implementation method utilized an interactive educational approach, incorporating instructional film screenings, material presentations on mitigation, disaster simulations, interactive quizzes, and Q&A sessions. Educational topics included the dangers of plastic waste, early warning signs of flooding, preventive behaviors, and safe self-evacuation procedures. The outcome demonstrated a significant improvement in students' understanding of waste management and safety measures during flood events. This activity proves that early disaster education and simulations effectively foster environmental responsibility and build school community resilience against disaster risks.